Allosteric modulators of solute carrier function: a theoretical framework - Boytsov, D.; Schicker, K.; Hellsberg, E.; Freissmuth, M.; Sandtner, W. (Frontiers in Physiology, 2023)
Large-scale drug screening is currently the basis for the identification of new chemical entities. This is a rather laborious approach, because a large number of compounds must be tested to cover the chemical space in an unbiased fashion. However, the structures of targetable proteins have become increasingly available. Thus, a new era has arguably been ushered in with the advent of methods, which allow for structure-based docking campaigns (i.e., virtual screens). Solute carriers (SLCs) are among the most promising drug targets. This claim is substantiated by the fact that a large fraction of the 400 SLC genes is associated with human diseases. The ability to dock large ligand libraries into selected structures of solute carriers has set the stage for rational drug design. However, in the present study, we show that these structure-based approaches can be refined by taking into account how SLCs operate. We specifically address the feasibility of targeting SLCs with allosteric modulators, because their actions differ fundamentally from those of ligands, which bind to the substrate binding site. For the pertinent analysis we used transition state theory in conjunction with the linear free energy relationship (LFER). These provide the theoretical framework to understand how allosteric modulators affect SLC-function.